Pengaruh Birthball Terhadap Intensitas Nyeri Kala I Persalinan - Madhona, Kiki Lestari; Jasmawati, Jasmawati; Raihanah, Siti (Akademi Kebidanan Bunga Husada Samarinda, 2023)
The process of childbirth culminates in the expulsion of the products of conception by the mother. During labor, the opening and flattening of the cervix will cause pain. Although this pain is subjective to each individual, it is believed that the use of a birthball during labor may reduce the severity of labor pain. The purpose of this study is to determine whether the use of a birthball can reduce labor pain. This study used a quasy experimental research design with a one group pretest posttest design without a control group design. the population in this study were mothers giving birth at AWS Hospital. Syahrani in february-March 2023, totaling 20 mothers who gave birth who met the inclusion and exclusion criteria. There is an influence between birthball intervention and labor pain where the z count is -3.771 with pvalue 0,001 < 0,05 (p < α). The use of a birthball for 40 minutes can be used as an alternative in reducing labor pain and optimizing the delivery of midwifery care to mothers in labor and also improving quality and health services. Birthballs are recommended for use in the delivery room to reduce labor pains